2017
DOI: 10.1111/jce.13156
|View full text |Cite
|
Sign up to set email alerts
|

Integrity of the Ganglionated Plexi Is Essential to Parasympathetic Innervation of the Atrioventricular Node by the Right Vagus Nerve

Abstract: The integrity of the GP is essential for the right vagus nerve to exert physiological effects of on AVN in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Animal studies have demonstrated that GPs on the right side act as “integration centers” and are capable of modulating the effect of stimulated left-sided GPs on AV and SA nodal responses [ 91 ]. HFS of the right inferior GPs has shown how they selectively innervate the AV node in humans [ 92 ]. As previously demonstrated in animal studies, ablation and mapping of right-sided GPs in humans with HFS can lower the number and magnitude of GP activity on the left side [ 93 ].…”
Section: Gp Ablation For Afmentioning
confidence: 99%
“…Animal studies have demonstrated that GPs on the right side act as “integration centers” and are capable of modulating the effect of stimulated left-sided GPs on AV and SA nodal responses [ 91 ]. HFS of the right inferior GPs has shown how they selectively innervate the AV node in humans [ 92 ]. As previously demonstrated in animal studies, ablation and mapping of right-sided GPs in humans with HFS can lower the number and magnitude of GP activity on the left side [ 93 ].…”
Section: Gp Ablation For Afmentioning
confidence: 99%
“…Vagus nerve exerts its influence on the AVN through the epicardial fat pads that are primarily located on the posterior wall of the left atrium ( 2 ). The inferior vena cava-left atrium fat pad (namely also right inferior GP) located around the coronary sinus mainly provides vagal innervations and selectively innervates the AVN in humans ( 2 , 3 ). It was shown that high-frequency stimulation of the right anterior (or superior right atrial vagal GP) and left superior GP (or superior left atrial vagal GP) could also influence the AVN ( 3 ).…”
mentioning
confidence: 99%
“…The inferior vena cava-left atrium fat pad (namely also right inferior GP) located around the coronary sinus mainly provides vagal innervations and selectively innervates the AVN in humans ( 2 , 3 ). It was shown that high-frequency stimulation of the right anterior (or superior right atrial vagal GP) and left superior GP (or superior left atrial vagal GP) could also influence the AVN ( 3 ). In addition, the influence of the right anterior GP on the AVN appears to be more important than its influence on the left superior GP ( 2 , 3 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations